Spectroscopic Characterization of Supramolecular Chiral Porphyrin Homoassociates at the Air–Water Interface. Issue 11 (November 2014) - Harada, Takunori; Moriyama, Hiroshi; Takahashi, Hiromi; Umemura, Kazuo; Yokota, Haruo; Kawakami, Ryo; Mishima, Kenji
The water-soluble 4-sulfonatophenyl meso-substituted porphyrin (TPPS) dye exhibits a transformation to a chiral self-aggregate from the non-aggregated species (diprotonated H4 TPPS 2– ) at low concentration (no more than 1 × 10 −5 M). Immobilization of supramolecular chiral porphyrin homoassociates was mediated by the electrostatic interaction between the anionic TPPS molecule and cationic surfactant monolayer at the air–water interface. With the immobilization, a reversible transformation from monomeric TPPS to J-aggregate ( M→J ) could be changed into an irreversible ( M→J ), which is desirable for stabilization of aggregation structure for a long period. The novel finding was achieved using a fine-tuned specialized solid-state circular dichroism (CD) spectrophotometer and derived analytical procedure to obtain artifact-free CD signals. To our knowledge, this is the first report achieving the chiral control of a homoassociate induced by a chiral surfactant at the air–water interface, indicating that the handedness of the formed homoassociate could be determined.